The States and Properties of Germanium in Sulfuric Acid Solution - Leiting Song; Haokai Di; Ming Liang; Yan Hong; Yiner Zeng; Kun Yang; Libo Zhang (Metals, 2023)
In recent years, with the development of science and technology, the strategic position of germanium is becoming more and more important, and the global demand for germanium is also increasing. At present, there is no unified description of the existence form of germanium in solutions. Based on the current mainstream acid leaching process of germanium, this paper studies the existing form and properties of germanium in sulfuric acid solutions. Through the characterization and analysis of Raman, FTIR, and XPS of three concentrations of pure germanium solution, it is clear that germanium mainly exists in the form of H2GeO3 and some Ge4+ in sulfuric acid solution. Through the Tyndall effect and zeta potential, it is determined that H2GeO3 exists in the form of colloid in sulfuric acid solution. With the increase of germanium concentration, H2GeO3 will polymerize in a sulfuric acid solution to form polygermanic acid, and the H2GeO3 colloidal dispersion system becomes more stable. This study clarifies the existing form and properties of germanium in sulfuric acid solution, which is of great significance to the leaching extraction of germanium-containing materials and the development of the germanium industry.